Pemenuhan Syarat Verlijden dalam Pembuatan Akta Autentik Terhadap Penghadap Penyandang Disabilitas Tunarungu (Studi Komparasi Undang-Undang Jabatan Notaris dan Kōshōninhō) - Ni Putu Sayuri Dewi; Sri Widyawati (Dinasti Research, 2025)
This research aims to analyze the obligation of Notary to analyze the obligations of notaries related to the fulfillment of the requirements for the reading of authentic deeds in the context of communication methods toward deaf visitors and to analyze the legal protection for deaf visitors in enhancing the accessibility of reading authentic deeds. The research method used in this writing is doctrinal legal research with a normative juridical approach. The result of this research by comparing the Indonesian Notary Law with Kōshōninhō, can be analyzed that the Indonesian Notary Law has not specifically regulated sign language interpreters for deaf people. Therefore, Indonesian can adopt the provision in Kōshōninhō, that the Notary is authorized to make authentic deeds for deaf persons accompanied by a certified sign language interpreter. Therefore, by having the notary state that the individual is a deaf visitors person and that a sign language interpreter assists in the reading of the deed, legal protection for deaf visitors can be achieved in the process of making an authentic deed before a Notary.